A Comparative Study of Compulsory Bequests (Wasiat Wajibah) in Islamic Inheritance Law: The Cases of Indonesia and Egypt - Bustomi, Ilham; Setyawan, Edy (Jurnal Syariah dan Hukum Komparatif, 2025)
This study presents a comparative legal analysis of wasiat wajibah (compulsory bequests) as implemented in Indonesia and Egypt, exploring how both Muslim-majority countries adapt Islamic inheritance principles to address the needs of non-heirs such as adopted children, stepchildren, and descendants of predeceased heirs. Rooted in classical Islamic jurisprudence, wasiat traditionally functioned as a voluntary bequest. However, modern legal systems in Indonesia and Egypt have transformed it into a compulsory mechanism to promote social justice and protect vulnerable individuals excluded under traditional fara’id rules. The study examines the integration of Sharia into national legal frameworks—Indonesia’s dual legal system and Egypt’s centralized civil law model—and analyzes key statutory provisions, judicial circulars, and landmark jurisprudence. Indonesian law, notably through the Kompilasi Hukum Islam and Supreme Court circulars, has broadened wasiat wajibah to include non-Muslim heirs and children of unregistered marriages. Egypt’s Law No. 71 of 1946 similarly mandates bequests for grandchildren. Through doctrinal and comparative methods, this study highlights both countries’ reliance on maslahah (public interest) and ijtihad (independent reasoning) in legal reform. The study concludes by addressing challenges related to legal certainty, access to justice, and the potential for broader Islamic legal modernization informed by context-sensitive interpretation.